(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
The article presents a mapping of the countless different discourses concerning don Giuseppe Morosini’s death, which is represented in the final shot of "Roma città aperta" (“Rome, Open City”) (Rossellini, 1945). The execution of Morosini, which took place on 3th April 1944 at Forte Bravetta, is located in a historical-political context that is highly problematic. Starting from a systematic research, the article compares all the testimonies and representations of the episode in order to highlight the link between the medium used, the historical context and the political-ideological interests of the period. The essay examines the relationship between chronicle, history and fiction in the representation of the priest’s death, leading us to reflect on the mechanisms and the reasons underlying the elaboration of the episode.